Relationship of Knowledge with the Implementation of OHS Management System in Regional General Hospital North Konawe District - Yasmin, Laode Muhammad; Jayadipraja, Erwin Azizi; Nunung, Nunung; Saafi, La Ode; Alista, Adnin (Public Health of Indonesia, 2025)
Background:The high incidence of accidents at the North Konawe District Hospital, coupled with the increasing demands for accreditation concerning employee protection, underscores the necessity for implementing an Occupational Health and Safety (OHS) management system at the hospital. Objectives:This study aims to examine the relationship between employees' knowledge and the application of the OHS management system at the North Konawe District Hospital. Method:This research employed a quantitative approach with a cross-sectional design. The study population consisted of all 115 employees at the North Konawe District Hospital. A sample of 89 participants was selected using simple random sampling. Data were gathered through a questionnaire, which was subsequently analyzed using the chi-square test and the Cramér’s V correlation coefficient. The instrument (questionnaire) underwent testing for validity and reliability, yielding satisfactory results. Results:The findings of this study reveal a moderate relationship between the level of knowledge and the application of the OHS management system at the North Konawe District Hospital. Data analysis using the chi-square test produced a p-value of 0.000 (p < 0.05), and the Cramér’s V coefficient was 0.600, indicating a medium-strength association between knowledge and the application of the OHS management system. Conclusion:Knowledge is a critical factor in shaping occupational health and safety behaviors within hospitals. Therefore, it is recommended that the management of the North Konawe District Hospital prioritize the enhancement of employees' knowledge through regular OHS training for all hospital staff. Keywords:knowledge; occupational health safety; Sulawesi Tenggara; Indonesia